1995
DOI: 10.1128/jb.177.7.1655-1661.1995
|View full text |Cite
|
Sign up to set email alerts
|

Activation of multiple antibiotic resistance and binding of stress-inducible promoters by Escherichia coli Rob protein

Abstract: Multiple antibiotic resistance in Escherichia coli can be mediated by induction of the SoxS or MarA protein, triggered by oxygen radicals (in the soxRS regulon) or certain antibiotics (in the marRAB regulon), respectively. These small proteins (SoxS, 107 residues; MarA, 127 residues) are homologous to the C terminus of the XylS-AraC family of proteins and are more closely related to a ϳ100-residue segment in the N terminus of Rob protein, which binds the right arm of the replication origin, oriC. We investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
188
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(199 citation statements)
references
References 44 publications
10
188
1
Order By: Relevance
“…It is known that permeability to antimicrobial agents, especially to small hydrophilic agents, through the outer membrane in E. coli greatly depends on the contents of OmpF and OmpC porin proteins, and that OmpF deficiency makes cells resistant to some antibiotics (Harder et al 1981;Cohen et al 1989;Ariza et al 1995;Thanassi et al 1995). The finding that the content of OmpF in strain OW66 was lower than that of strain OW6, even in the absence of CTAB, strongly suggests dependency of the resistance of the mutant on the OmpF level in the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that permeability to antimicrobial agents, especially to small hydrophilic agents, through the outer membrane in E. coli greatly depends on the contents of OmpF and OmpC porin proteins, and that OmpF deficiency makes cells resistant to some antibiotics (Harder et al 1981;Cohen et al 1989;Ariza et al 1995;Thanassi et al 1995). The finding that the content of OmpF in strain OW66 was lower than that of strain OW6, even in the absence of CTAB, strongly suggests dependency of the resistance of the mutant on the OmpF level in the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with Rob, a MarA and SoxS paralogue, showed that it could function in a similar manner (Ariza et al, 1995). Subsequent data have documented multidrug-resistant clinical strains of E. coli (Linde et al, 2000;Maneewannakul & Levy, 1996) and Salmonella enterica serovar Typhimurium (S. typhimurium) (Koutsolioutsou et al, 2001) that constitutively express AraC family members.…”
Section: Introductionmentioning
confidence: 94%
“…For example, the E. coli proteins MarA, Rob and SoxS all target genes involved in the oxidative stress response and bind to closely related DNA sequences. However, some targets respond differently from these proteins (Ariza et al, 1995;Jair et al, 1995;Li & Demple, 1996).…”
Section: Comparison Of Natural and Selex Sitesmentioning
confidence: 99%